Wpływ pokarmu na rozwój chrząszczy chrabąszcza kasztanowca (Melolontha hippocastani F.) (Coleoptera, Melolonthidae) - Woreta, Danuta; Sukovata, Lidia (Leśne Prace Badawcze, 2010)
This paper presents the results of the studies of life duration, survival, weight and fecundity of the forest cockchafer Melolontha hippocastani beetles feeding on Quercus robur , Carpinus betulus , Betula pendula and Alnus glutinosa . Beetles were collected from soil in mid April 2009, before their emergence. Five males and five females per tree species in 6 replications were reared from 28 April through 4 May 2009. Ten females were taken out from each tree species on 5 May for individual rearing and fecundity estimation. Observations were conducted till 17 June. Average life duration of females was 23.6, 20, 19.3 and 11.1 days on oak, birch, hornbeam and alder leaves, respectively. Lifetime of males was shorter than of females on all tree species except oak. Survival of both males and females was the highest on oak, whereas the mortality on alder reached 100% after 10 days in males and after 15 days in females. Substantial changes in a weight was observed mainly during the first six days of rearing. An increase of female weight was 37.3, 20.7, 14.2 and 4.2% on oak, hornbeam, birch and alder leaves, respectively. The significant increase on oak was observed already after two days. Changes in weight on birch and alder were not significant. Female weight on oak was significantly higher than on birch and alder leaves. Females on the hornbeam grew slightly better than on the latter species and slightly worse than on oak. Contrary to expectations the male weight decreased with time, although significant changes were only on birch and alder leaves. Nine of 10 females feeding on oak leaves deposited 15–68 eggs/female (37.4 eggs/female on the average), whereas there was the only one female that laid eggs among those feeding on hornbeam leaves. Females on birch and alder did not deposit eggs at all. Oak leaves appeared to be the most favorable food for the forest cockchafer beetles in relation to life duration, survival, weight and fecundity, whereas alder was the least suitable. Obtained results will be useful in tree species selection for reforestation, particularly in regions highly infested by forest cockchafers.